The tongue as a gateway to voice, resonance, style, and intelligibility - Nair, Angelika (San Diego, CA : Plural Publishing, Inc., 2021)
"To be in the way, or to be out of the way, that is the question. Voice users and scientists alike agree that the tongue is a crucial part in singing. Yet, there has been no literature published that solely addresses the tongue and its acoustical influence in the context of technique. The Tongue as a Gateway to Voice, Resonance, Style, and Intelligibility finally answers the question which has plagued voice users: how does the tongue affect my singing and how can I manipulate it for my purpose? This book is unique in its approach to, and concentration on, the singing and speaking of consonants. In the world of voice, consonants are often overlooked, in favor of a vowel-centric approach to vocal pedagogy. By combining voice pedagogy with vocal science, Angelika Nair breaks down the mysteries of the tongue and its effect on consonant production for a fascinating new take on the human voice"--
It's a Vowel-Centric World -- Anatomy and Physiology -- Principle of Resonance Creation-The Low Mandible Maneuver -- Watch Your Tongue -- The Building Blocks of Language and the Biofeedback Ultrasound -- Vowels and Vowels That You Thought Were Consonants -- Consonants and Consonant Resonance (CR) -- Nasal and Continuant Consonants -- Stop Consonants -- Pre-Voiced Stop Consonants -- Mid/Back Fricatives and the Aspirate -- Front Fricatives -- Front Voice Fricatives -- Rhotic, Non-English R-Sounds -- Affricates and Para-Affricates.
P.B
P.B
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Voice -- Physiological aspects; Speech -- Physiological aspects; Singing; Tongue; Voice -- physiology; Tongue -- physiology; Speech -- physiology; Tongue; Parole -- Aspect physiologique; Chant; Langue (Anatomie); chants; Singing; Speech -- Physiological aspects; Tongue; Voice -- Physiological aspects; Electronic books